The Effect of the Covid 19 Virus and Online Learning on English Subjects in Elementary Schools - Prasetyo, Dhaniel; Rudini, Rudini; Prayogi, Ryan; Rahmawati, Ilham; Syah Putra, Arman (CV. Inara, 2021)
Elementary school is a medium used by the government to provide proper education for its people. With the existence of an elementary school, the community through education with various kinds of subjects that can be used as a basis so that the Indonesian nation can develop in the future with 6 years of compulsory education and 9 years of compulsory education Indonesia is good enough and illiteracy has begun to be eliminated by the existence of compulsory education, therefore a good education is education that can cover all corners of Indonesia and can be felt by all Indonesian people so that the Indonesian nation can become an advanced nation with education as the spearhead from Indonesia. Quantitative research is the method used in this study by emphasizing survey tools conducted to 100 people who were randomly selected in order to get very accurate data and real data in the field. Therefore, by using this method, the research can be continued so that it can find answers of the research problem raised. The variables studied in schools during the pandemic are online learning systems, offline learning systems and many more variables studied by researchers so they can find out which variables can affect the teaching and learning system in Indonesia, especially in the teaching and learning system in Indonesia. Elementary schools with these variables will be able to develop which things are good and which things are bad can be reduced. In this study will produce a data that has been processed on a system that uses SPSS tools. Therefore, with the processing of these data, it can be seen which variables affect elementary schools.